ANALISIS DAMPAK PENYALURAN BANTUAN LANGSUNG TUNAI (BLT) DALAM PEMULIHAN PEREKONOMIAN MASYARAKAT AKIBAT - eka chyntia; Eko Gani PG; Mulia Andirfa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Perppu No. 1 of 2020 provides a new instrument to minimize the impact of the Covid-19 pandemic on the village economy. Article 2 Paragraph (1) letter (i) of the regulation states that it is necessary to prioritize the use of budget allocations for certain activities (refocusing), adjustment of allocations, and/or cutting/delaying the distribution of budget transfers to regions and village funds, with certain criteria. Furthermore, in the explanation of the Perppu it is stated that what is meant by "prioritizing the use of village funds" is that village funds can be used, among others, for direct cash assistance (BLT) for the poor in villages and activities to handle the Covid 19 pandemic. The problem that is the focus of this research is how the impact of distributing BLT to the Paloh Lada gampong community in supporting the family economy. And also the effectiveness of the implementation of BLT as well as obstacles in economic recovery in the village. This study aims to see whether BLT can ease the economy of the community affected by COVID-19 and whether the BLT that has been provided can support the economy of families and villages in Paloh Lada Village, especially in Dewantara District. The research method used is the interview method either directly or by distributing google form. The sample is the Paloh Lada village community who are included in the BLT recipient category during the covid-19 pandemic. Data were analyzed using descriptive qualitative data analysis. The results of this study show that the community is greatly helped by the BLTDD provided by the Government through the Village Fund. The community's economy is slowly starting to bounce back after the COVID-19 pandemic.